SCREENING OF POTENTIAL DRUG-DRUG INTERACTIONS AMONG GERIATRIC PATIENTS POST-CARDIAC SURGERY: INSIGHTS FROM MICROMEDEX AND LEXIDRUG (The Research of Medical Science Review, 2025)
Background: The global increase in the ageing population has heightened the Prevalence of cardiovascular diseases (CVD), particularly in Pakistan. Older patients, especially those undergoing cardiac surgery, are at significant risk for polypharmacy and potential drug-drug interactions (pDDIs), which can lead to adverse clinical outcomes. However, the Prevalence of pDDIs in geriatric cardiac surgery patients has not been thoroughly explored in Pakistan. Objective: This study is designed to evaluate the Prevalence, severity, and types of pDDIs in geriatric patients post-cardiac surgery, utilizing two widely used drug interaction databases, Micromedex and Lexidrug. The study further explored the relationship between polypharmacy and the Prevalence of pDDIs. Methods: An observational study was conducted on 96 geriatric patients (age ≥ 60 years) who underwent cardiac surgery at a tertiary care hospital in Pakistan. Sociodemographic and clinical data were collected, including information on comorbidities, surgical procedures, and prescribed medications. pDDIs were screened using Micromedex and Lexidrug databases, which categorize interactions by severity, onset, and documented evidence (Micromedex) or risk ratings (Lexidrug). Statistical analysis was performed to assess associations between polypharmacy and pDDIs. Results: The study revealed a high prevalence of pDDIs, with 98.5% and 100% of patients having at least one interaction identified by Micromedex and Lexidrug, respectively. Most pDDIs were classified as major (66.4% by Micromedex and 61.5% by Lexidrug). A significant association was found between the prescribed drugs and the Prevalence of pDDIs, with polypharmacy (≥11 drugs) significantly increasing the risk of interactions. Commonly identified high-risk drug pairs included aspirin-clopidogrel, aspirin-furosemide, and clopidogrel-omeprazole. Conclusions: This study reveals a high prevalence of pDDIs in geriatric cardiac surgery patients, with 98.5% and 100% identified by Micromedex and Lexidrug, respectively. Most interactions were classified as major, with polypharmacy strongly linked to increased pDDIs. High-risk drug combinations, such as aspirin and clopidogrel, were common. These findings emphasize the need for practical drug-drug interaction screening tools to improve medication safety, particularly in resource-limited settings.